A highly efficient genetic transformation system for broccoli and subcellular localization - Zhao, Yongyu; Yang, Dongxu; Liu, Yumei; Han, Fengqing; Li, Zhansheng (Frontiers in Plant Science, 2023)
Agrobacterium-mediated genetic transformation has been widely used for the identification of functional genes and regulatory and developmental mechanisms in plants. However, there are still some problems of low genetic transformation efficiency and high genotype dependence in cruciferous crops. In this study, broccoli, a worldwide Brassica crop, was used to investigate the effects of genotype, explant type, concentration of hygromycin B used during seedling selection, overexpression vector type, RNAi and CRISPR/cas9 on the genetic transformation efficiency. At the same time, two vectors, PHG-031350 and PHG-CRa, were used for subcellular localization of the glucoraphanin synthesis-related gene FMOGS-OX5 and clubroot resistance gene by a PEG-Ca2+-mediated transient transformation system for broccoli protoplasts. Finally, the Agrobacterium-mediated genetic transformation system of broccoli was optimized and improved. This study showed that hypocotyl explants are more suitable for Agrobacterium-mediated transgene and CRISPR/Cas9 gene editing of broccoli. In contrast to previous studies, we found that 5 mg/L hygromycin B was more advantageous for the selection of resistant broccoli sprouts, and genotype 19B42 reached the highest transformation rate of 26.96%, which is higher than that in Brassica oleracea crops. In addition, the inbred line 19B42 successfully achieved high genetic transformation of overexpression, RNAi and CRISPR/Cas9 vectors; thus, it is powerful recipient material for the genetic transformation of broccoli. Subcellular localization proved that the glucoraphanin metabolism-related gene Bol031350 and clubroot resistance gene CRa were both expressed in the nucleus, which provided a scientific basis for studying the regulation of glucosinolate metabolism and clubroot resistance in cruciferous crops. Therefore, these findings will provide new insight into the improvement of the genetic transformation and molecular breeding of Brassica oleracea crops.